Environmentally friendly packaging bag material for freeze-dried yogurt fruit particles and its preparation process

By grafting a new sensitizer on the surface of the nanophotosensitive filler, forming a core-shell structure photosensitive agent, and adopting a high-speed solvent-free composite process, the problem of difficult degradation of traditional polyethylene packaging materials is solved, and the excellent photodegradation performance and recycling function of freeze-dried yogurt fruit packaging materials are achieved.

CN118650952BActive Publication Date: 2025-04-25SUZHOU ZIJIN PLASTIC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202410904746.9
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-07-08
Publication Date
2025-04-25
Estimated Expiration
2044-07-08

AI Technical Summary

Technical Problem

Traditional polyethylene plastic packaging materials are difficult to degrade, resulting in environmental pollution. The existing photodegradable polyethylene materials still have room for improvement in degradation performance and recycling.

Method used

By synthesizing two new sensitizers and uniformly grafting them on the surface of the nanophotosensitive filler through esterification reaction, a core-shell structure photosensitive agent was formed. Combined with a high-speed solvent-free composite process, a composite film with excellent photodegradation performance and recycling function was prepared.

Benefits of technology

It realizes the ultraviolet degradation performance of freeze-dried yogurt fruit packaging materials, has high barrier properties and mechanical properties, meets hygiene indicators, and supports recycling.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118650952B_ABST
    Figure CN118650952B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of freeze-dried yogurt fruit grain packaging material research and development, and discloses a freeze-dried yogurt fruit grain environmentally friendly packaging bag material and its preparation process, including: preparing a carboxylic acid functionalized sensitizer, the carboxylic acid functionalized sensitizer is sensitizer I and / or sensitizer II; preparing a nano-photosensitive filler with a surface modified with a hydroxyl functional group; by a chemical bonding method of an esterification reaction, the sensitizer is uniformly grafted on the surface of the nano-photosensitive filler to construct a core-shell structure photosensitizer; a high-speed solvent-free composite process is used to bond the BOPE surface layer, the barrier middle layer and the PE inner layer to prepare a composite film, and the composite film contains a core-shell structure photosensitizer. The present invention provides a method for preparing a composite film, and a freeze-dried yogurt fruit grain packaging material with excellent degradation performance and in compliance with safety standards is prepared, which has the characteristics of material integration and can realize recycling function.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of research and development of freeze-dried yogurt fruit-grain packaging materials, in particular to an environment-friendly packaging bag material for freeze-dried yogurt fruit-grain and a preparation process thereof. Background Art

[0002] Freeze-dried yogurt fruit particles are favored by consumers because of their fun, easy operation and high nutritional value. At present, the packaging materials used for freeze-dried yogurt fruit particles on the market are plastic packaging films made of polyethylene, polypropylene, polystyrene and polyethylene terephthalate. Among them, polyethylene is widely used due to its advantages such as good chemical stability, good toughness and easy processing. It has become the most used plastic packaging film material and plays a pivotal role. However, traditional polyethylene plastics have high molecular weight, stable structure and are difficult to degrade. When they are discarded at will, they will cause serious environmental problems and become one of the main sources of white pollution.

[0003] The search found that photodegradable polyethylene material refers to the process of decomposing polyethylene material into small molecular compounds through photochemical reaction under light conditions. Currently, adding photosensitizers is the main means to improve the photodegradation performance of polyethylene materials. The patent with authorization number CN114044961B discloses a photodegradable environmentally friendly plastic packaging bag and its production process. By using polyethylene, cross-linking agent, dispersant, plasticizer, photosensitizer, photosensitizer, compatibilizer, conversion agent and other raw materials to prepare plastic packaging bags, the degradation ability of plastic packaging bags can be effectively improved.

[0004] Further search revealed that commonly used photosensitizers mainly include inorganic photosensitizers and organic photosensitizers. Among them, titanium dioxide can absorb light energy to excite electrons, form electron-hole pairs, participate in redox reactions, and produce active oxygen species. It is the most widely used inorganic photosensitizer; organic small molecules with large conjugated structures have excellent light absorption and can be used as organic photosensitizers to achieve photodegradation of materials. Using organic small molecule photosensitizers to surface-graft titanium dioxide inorganic photosensitizers can not only improve the dispersibility and interface compatibility of titanium dioxide, but also synergistically enhance the photodegradation ability of the material. Summary of the invention

[0005] The invention provides an environment-friendly packaging bag material for freeze-dried yogurt fruit particles and a preparation process thereof. Firstly, two new sensitizers are synthesized, and then the sensitizers are uniformly grafted onto the surface of a nano-photosensitive filler for modification by a chemical bonding method, thereby achieving the technical effects of improving interface compatibility, broadening absorption wavelength, and enhancing degradation ability. On this basis, a high-speed solvent-free composite process is adopted to prepare an environment-friendly packaging bag material for freeze-dried yogurt fruit particles, which has excellent light degradation performance and can be recycled.

[0006] A preparation process of an environmentally friendly packaging bag material for freeze-dried yogurt fruit particles comprises the following steps:

[0007] Step 1: preparing a carboxylic acid functionalized sensitizer, wherein the carboxylic acid functionalized sensitizer is sensitizer I and / or sensitizer II;

[0008] Step 2: preparing a nanometer photosensitive filler with a surface modified with a hydroxyl functional group, wherein the nanometer photosensitive filler is a hydroxylated titanium dioxide nanoparticle;

[0009] Step 3: The sensitizer is uniformly grafted onto the surface of the nano-photosensitive filler through a chemical bonding method of an esterification reaction to construct a core-shell structured photosensitizer;

[0010] Step 4: The BOPE surface layer, the barrier middle layer and the PE inner layer are bonded by a high-speed solvent-free composite process to prepare a composite film, and the composite film contains a core-shell structure photosensitizer.

[0011] Preferably, the preparation method of the sensitizer I is:

[0012] Step S1-1: utilizing the Hantzsch reaction mechanism to catalyze the condensation reaction of p-phenylbenzaldehyde, butyl acetoacetate and ammonium acetate with a phase transfer catalyst to generate a biphenyl ester dihydropyridine monomer;

[0013] Step S1-2: using sodium nitrite as an oxidant, catalyzing an organic protonic acid to cause an oxidation reaction of the dihydropyridine group of the biphenyl ester dihydropyridine monomer to generate a biphenyl ester pyridine monomer;

[0014] Step S1-3: Under alkaline conditions, the butyl carboxylate functional group of the biphenyl ester pyridine monomer undergoes a hydrolysis reaction to generate a sensitizer I.

[0015] Preferably, the preparation method of the sensitizer II is:

[0016] Step S2-1: using the Hantzsch reaction mechanism, catalyzing the condensation reaction of 4,4'-biphenyldicarboxaldehyde, butyl acetoacetate and ammonium acetate with a phase transfer catalyst to generate a biphenyl bis(ester dihydropyridyl) monomer;

[0017] Step S2-2: using sodium nitrite as an oxidant, catalyzing an organic protonic acid to cause an oxidation reaction of the dihydropyridine group of the biphenyl bis(ester dihydropyridyl) monomer to generate a biphenyl bis(ester dihydropyridyl) monomer;

[0018] Step S2-3: Under alkaline conditions, the carboxylic acid butyl ester functional group of the biphenyl bis(ester pyridyl) monomer undergoes a hydrolysis reaction to generate a sensitizer II.

[0019] Preferably, the preparation method of the composite film in step 4 is:

[0020] Step S3-1: using a core-shell structure photosensitizer as a degradation modifier and a low-density polyethylene resin as a raw material, through blending, melting, extrusion, first longitudinally and then transversely stretching, and finally hot pressing to shape, a BOPE surface layer is obtained;

[0021] Step S3-2: using a core-shell structure photosensitizer as a degradation modifier and ethylene-vinyl alcohol copolymer resin as a raw material, blending, melting, extruding, pelletizing, and finally casting into a film to obtain a barrier intermediate layer;

[0022] Step S3-3: using a core-shell structure photosensitizer as a degradation modifier and a low-density polyethylene resin as a raw material through blending, melting, extrusion, pelletizing, and finally casting into a film to obtain a PE inner layer;

[0023] Step S3-4: A high-speed solvent-free laminating machine is used to bond the BOPE surface layer, the barrier middle layer and the PE inner layer to obtain a composite film with a thickness of 80 to 120 μm.

[0024] Preferably, the core-shell structured photosensitizer is photosensitizer I, and the preparation method of the photosensitizer I is: based on the esterification reaction mechanism, sensitizer I is modified on the surface of hydroxylated nano-titanium dioxide to prepare photosensitizer I.

[0025] Preferably, the core-shell structure photosensitizer is photosensitizer II, and the preparation method of photosensitizer II is: based on the esterification reaction mechanism, sensitizer II is modified on the surface of hydroxylated nano-titanium dioxide to prepare photosensitizer II.

[0026] The freeze-dried yogurt fruit-grain environmentally friendly packaging bag material prepared according to the above process is a composite film, which is prepared by bonding a BOPE surface layer, a barrier middle layer and a PE inner layer using a high-speed solvent-free composite process, and the composite film contains a core-shell structure photosensitizer.

[0027] The freeze-dried yogurt fruit-grain environmentally friendly packaging bag material prepared according to the process has a tensile strength of 26-30 MPa, an elongation at break of 420-460%, and can be recycled through ultraviolet degradation.

[0028] The composite film prepared according to the above process is used in the environmentally friendly packaging of freeze-dried yogurt fruit particles.

[0029] Beneficial Effects

[0030] The invention firstly utilizes Hantzsch reaction, oxidation reaction and hydrolysis reaction to synthesize a carboxyl functionalized sensitizer, and then based on the esterification reaction mechanism, the sensitizer is modified on the surface of hydroxylated nano titanium dioxide to prepare a core-shell structure photosensitizer; finally, the core-shell structure photosensitizer is used as a degradation modifier, and a high-speed solvent-free composite process is adopted to prepare a composite film. Experimental results show that the composite film has ultraviolet light degradation performance, and at the same time has high barrier performance and mechanical properties, and meets hygiene indicators, and can be used in environmentally friendly packaging of freeze-dried yogurt fruit particles;

[0031] The composite membrane prepared by the present invention has the characteristics of material integration and can realize the function of recycling. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 This is the synthetic route of sensitizer Ⅰ;

[0033] Figure 2 This is the synthetic route of sensitizer II;

[0034] Figure 3 The experimental results of mechanical properties of composite films before and after UV irradiation. DETAILED DESCRIPTION

[0035] Experimental example:

[0036] Experiment 1: Preparation of sensitizer Ⅰ, such as Figure 1 As shown, the synthesis process is as follows:

[0037] (1) Synthesis of biphenyl ester dihydropyridyl monomer: using the Hantzsch reaction mechanism, p-phenylbenzaldehyde, butyl acetoacetate and ammonium acetate are catalyzed by a phase transfer catalyst to undergo a condensation reaction to generate a biphenyl ester dihydropyridyl monomer;

[0038] Among them, the phase transfer catalyst is selected from one of tetrabutylammonium bromide, tetraethylammonium bromide, tetrabutylammonium chloride, and benzyltriethylammonium chloride; in this experimental example, benzyltriethylammonium chloride is selected;

[0039] The specific reaction steps for synthesizing the biphenyl ester dihydropyridyl monomer are as follows: 1.8 g of p-phenylbenzaldehyde, 1.6 g of butyl acetoacetate, 1.9 g of ammonium acetate, 0.9 g of benzyltriethylammonium chloride and 50 mL of deionized water are added to a round-bottom flask, the temperature is raised to 90° C. and stirred for reaction for 3 h, the reaction process is monitored by thin layer chromatography (developing solvent: dichloromethane: cyclohexane=1:2 ratio), cooling, suction filtering, washing with deionized water, and recrystallization with ethanol to obtain the biphenyl ester dihydropyridyl monomer;

[0040] (2) Synthesis of biphenyl ester pyridyl monomer: using sodium nitrite as an oxidant, an organic protonic acid catalyzes an oxidation reaction of the dihydropyridine group of the biphenyl ester dihydropyridyl monomer to generate a biphenyl ester pyridyl monomer;

[0041] Among them, the organic protonic acid catalyst is selected to use formic acid or acetic acid; in this experimental example, acetic acid is selected;

[0042] The specific reaction steps for synthesizing the biphenyl ester pyridine monomer are as follows: 4.6 g of the biphenyl ester dihydropyridine monomer and 10 mL of acetic acid are added to a round-bottom flask, stirred and dissolved for 30 minutes, then 0.7 g of sodium nitrite is added to the round-bottom flask three times, the temperature is raised to 65° C., stirred and reacted for 4 hours, and after cooling, 120 mL of ice-water mixture is added to dilute, and the pH is adjusted to 7 by neutralization with ammonia water, filtered, washed with deionized water, and dried to obtain the biphenyl ester pyridine monomer;

[0043] (3) Synthesis of sensitizer I: Under alkaline conditions, the carboxylic acid butyl ester functional group of the biphenyl ester pyridine monomer undergoes a hydrolysis reaction to generate sensitizer I;

[0044] The specific reaction steps for synthesizing sensitizer I are as follows: 4.6 g of biphenyl ester pyridine monomer and 50 mL of methanol are added to a round-bottom flask, heated to 30°C for dissolution for 30 min under mechanical stirring, then 50 mL of 35 wt% NaOH aqueous solution is added to the flask, heated to 70°C for stirring and reacting for 5 h, cooled to room temperature and placed for 12 h, rotary evaporated, neutralized with hydrochloric acid to adjust pH=5, extracted with dichloromethane, rotary evaporated, recrystallized, and dried to obtain sensitizer I, and its hydrogen spectrum characterization results are as follows: 1 HNMR (CDCl3, 400MHz) δ: 2.50 (s, 6H, -CH3), 7.36-7.63 (m, 9H, Ar-H).

[0045] Experiment 2: Preparation of sensitizer II, such as Figure 2 As shown, the synthesis process is as follows:

[0046] (1) Synthesis of biphenyl bis(ester dihydropyridyl) monomer: Using the Hantzsch reaction mechanism, 4,4'-biphenyl dicarboxaldehyde, butyl acetoacetate and ammonium acetate are catalyzed by a phase transfer catalyst to undergo a condensation reaction to generate a biphenyl bis(ester dihydropyridyl) monomer. The synthesis steps and synthesis reaction conditions refer to the synthesis experiment of the biphenyl ester dihydropyridyl monomer. The difference between the synthesis experiment of the biphenyl ester dihydropyridyl monomer and the synthesis experiment of the biphenyl ester dihydropyridyl monomer is that 1.1 g of 4,4'-biphenyl dicarboxaldehyde is used to replace 1.8 g of p-phenylbenzaldehyde;

[0047] (2) Synthesis of biphenyl bis(ester pyridyl) monomer: Sodium nitrite is used as an oxidant, and an organic protonic acid is used to catalyze the oxidation reaction of the dihydropyridine group of the biphenyl bis(ester dihydropyridyl) monomer to generate a biphenyl bis(ester pyridyl) monomer. The synthesis steps and synthesis reaction conditions refer to the synthesis experiment of the biphenyl ester pyridyl monomer. The difference between the synthesis experiment of the biphenyl ester pyridyl monomer and the synthesis experiment of the biphenyl ester pyridyl monomer is that 3.9 g of the biphenyl bis(ester dihydropyridyl) monomer is used to replace 4.6 g of the biphenyl ester dihydropyridyl monomer.

[0048] (3) Synthesis of sensitizer II: Under alkaline conditions, the carboxylic acid butyl ester functional group of the biphenyl bis(ester pyridyl) monomer undergoes a hydrolysis reaction to generate sensitizer II, and its hydrogen spectrum characterization results are as follows: 1 H NMR (CDCl3, 400MHz) δ: 2.53 (s, 12H, -CH3), 7.58-7.68 (m, 9H, Ar-H);

[0049] The synthesis steps and reaction conditions of sensitizer II refer to the synthesis experiment of sensitizer I. The difference between it and the synthesis experiment of sensitizer I is that 4.3g of biphenyl bis(ester pyridyl) monomer is used to replace 4.6g of biphenyl ester pyridyl monomer.

[0050] Embodiment 1:

[0051] Preparation of photosensitizer I: Based on the esterification reaction mechanism, sensitizer I was modified on the surface of hydroxylated nano-titanium dioxide to prepare photosensitizer I. The specific experimental steps are as follows: 5 g of hydroxylated titanium dioxide nanoparticles and 50 mL of N, N-dimethylformamide were added to a round-bottom flask, and evenly dispersed by ultrasonication for 1 h. Then, 10 mL of sensitizer I solution (prepared by 1 g of sensitizer I and 10 mL of N, N-dimethylformamide) and 2 mL of concentrated sulfuric acid were added dropwise to the flask under mechanical stirring. The temperature was raised to 70 ° C and stirred for 12 h. After cooling, it was centrifuged at 3000 rpm for 5 min, washed with ethanol, and dried to obtain photosensitizer I.

[0052] Preparation of photosensitizer II: Based on the esterification reaction mechanism, sensitizer II is modified on the surface of hydroxylated nano-titanium dioxide to prepare photosensitizer II. The preparation method is as follows: sensitizer II is used to replace the above sensitizer I, referring to the preparation steps and experimental conditions of photosensitizer I, to prepare photosensitizer II;

[0053] Among them, the preparation steps of hydroxylated nano-titanium dioxide are: 1.5mL concentrated hydrochloric acid, 4.5mL glacial acetic acid, 2.5mL tetrabutyl iron ester and 2.5g surfactant SDS (sodium dodecyl sulfate) are added to 30mL anhydrous ethanol in sequence, stirred vigorously to a clear and transparent colloid, heated to 40°C and stirred for 6h, aged in an oven at 65°C for 24h, then placed in a muffle furnace and heated to 500°C for calcination for 6h, washed with distilled water and dried after cooling to obtain hydroxylated titanium dioxide nanoparticles with an average diameter of 60 to 80nm.

[0054] Embodiment 2:

[0055] (1) preparing composite membrane I, comprising the following steps:

[0056] Step 1, preparing a BOPE surface layer: adding 45g of low-density polyethylene resin and 1.5g of photosensitizer I to a twin-screw extruder preheated to 140°C, blending, melting, and extruding through the twin-screw extruder, and then successively stretching them longitudinally and then transversely, the temperature during longitudinal stretching is 80°C, the stretching ratio is 5 times, the temperature during transverse stretching is 150°C, the stretching ratio is 6 times, and finally hot pressing is performed at 140°C to obtain a BOPE surface layer;

[0057] Among them, the process parameters of the twin-screw extruder corresponding to the BOPE surface layer are set as follows: the temperatures of zones 1-3 are 110°C, 140°C, and 160°C, respectively, the flow channel temperature is 150°C, and the speed is 30r / min;

[0058] Step 2, preparing a barrier intermediate layer: adding 15g of ethylene-vinyl alcohol copolymer resin, 30g of low-density polyethylene resin and 1.5g of photosensitizer I into a twin-screw extruder preheated to 170°C, blending, melting and extruding through the twin-screw extruder, cutting them with a pelletizer to obtain 1-5mm particles, and then directly adding them to a casting machine preheated to 170°C, casting into a film, and obtaining a barrier intermediate layer;

[0059] Among them, the process parameters of the twin-screw extruder corresponding to the barrier middle layer are set as follows: the temperatures of zones 1-3 are 160°C, 185°C, and 200°C, respectively, the flow channel temperature is 195°C, and the rotation speed is 40r / min;

[0060] Step 3, preparing the PE inner layer: adding 45g of low-density polyethylene resin and 1.5g of photosensitizer I into a twin-screw extruder preheated to 140°C, blending, melting and extruding through the twin-screw extruder, cutting them with a pelletizer to obtain 1-5mm particles, and then directly adding them to a casting machine preheated to 140°C, casting into a film, and obtaining a PE inner layer;

[0061] Among them, the process parameters of the twin-screw extruder corresponding to the PE inner layer are set as follows: the temperatures of zones 1-3 are 110°C, 140°C, and 160°C, respectively, the flow channel temperature is 150°C, and the rotation speed is 30r / min;

[0062] Step 4, preparing composite film I: using a high-speed solvent-free composite machine to bond the BOPE surface layer, the barrier middle layer and the PE inner layer together, the composite speed is 500m / min, the composite temperature is 40°C, the cooling temperature is 20°C, the composite pressure is 0.4Mpa, and the gluing pressure is 0.5Mpa, to obtain a composite film I with a thickness of 100μm;

[0063] Among them, the low-density polyethylene resin was purchased from CNOOC Shell Petrochemical Co., Ltd., with the specifications of 2420H, Mn~180000, MFR 2.0~2.5g / 10min; the ethylene-vinyl alcohol copolymer resin was purchased from Dongguan Kaisi Li Plastic Raw Materials Co., Ltd., with the specifications of E105B, Mn~10000, ethylene content 44%.

[0064] (2) Preparation of composite membrane II: using photosensitizer II instead of the above photosensitizer I, referring to the preparation steps and experimental conditions of composite membrane I, to prepare composite membrane II;

[0065] (3) Preparation of composite membrane: Referring to the preparation steps and experimental conditions of composite membrane I, a composite membrane was prepared without using photosensitizer I as a comparative example.

[0066] Performance Test:

[0067] (1) The elongation at break and tensile strength of the sample were tested using an Instron 5565 universal tensile testing machine. The specific test steps are as follows: a 30 mm × 5 mm sample was fixed on the tensile testing machine and a tensile test was performed at a tensile rate of 5 mm / min;

[0068] (2) An artificial accelerated ultraviolet degradation test was conducted using a LUV-1 ultraviolet aging test chamber, which had three 20W ultraviolet high-pressure mercury lamps built in. The main irradiation wavelength of the ultraviolet lamp was 295nm. The specific test steps were as follows: a 50cm×8cm film sample was placed under the ultraviolet lamp for irradiation. The film sample was distributed in the effective light area and the distance from the lamp tube was 14.5cm. The ambient temperature was 25°C. After irradiation for 5 days, the film sample was taken out and the tensile properties were tested according to the method in step (1).

[0069] (3) Place a 30 cm round sample in a glass desiccator at an ambient temperature of 25°C and use anhydrous calcium chloride as a desiccant for 72 hours. Then use a Y110 oxygen permeability tester and a W3 / 060 water vapor permeability tester to test the barrier properties of the sample.

[0070] (4) Test the hygienic properties of the samples according to GB / T 5009.60-2003 “Analytical methods for hygienic standards of polyethylene, polystyrene and polypropylene moldings for food packaging”;

[0071] The above experimental results are shown in Tables 1-3 below.

[0072] Table 1 Experimental results of mechanical properties of composite membranes

[0073]

[0074] Table 2 Barrier performance test results of composite films

[0075]

[0076]

[0077] Table 3 Hygienic performance test results of composite membrane

[0078]

[0079] Note: The physical and chemical indicators of the experimental results are based on GB / T 5009.58-2003 "Analysis Methods for Hygienic Standards of Polyethylene Resins for Food Packaging";

[0080] According to the elongation at break change rate data in Table 1, the Figure 3 Through comprehensive analysis of the above experimental results, the following conclusions can be drawn: Composite film I and composite film II both have UV degradation properties, and at the same time have high barrier properties and mechanical properties, and meet the hygiene indicators, and can be used in environmentally friendly packaging of freeze-dried yogurt fruit particles.

Claims

1. A preparation process of an environmentally friendly packaging bag material for freeze-dried yogurt fruit particles, characterized in that: The following steps are involved: Step 1: preparing a carboxylic acid functionalized sensitizer, wherein the carboxylic acid functionalized sensitizer is sensitizer I and / or sensitizer II; Step 2: preparing a nanometer photosensitive filler with a surface modified with a hydroxyl functional group, wherein the nanometer photosensitive filler is a hydroxylated titanium dioxide nanoparticle; Step 3: The sensitizer is uniformly grafted onto the surface of the nano-photosensitive filler through a chemical bonding method of an esterification reaction to construct a core-shell structured photosensitizer; Step 4: The BOPE surface layer, the barrier middle layer and the PE inner layer are bonded by a high-speed solvent-free composite process to prepare a composite film, wherein the composite film contains a core-shell structure photosensitizer; The preparation method of the sensitizer I is: Step S2-1: using the Hantzsch reaction mechanism, catalyzing the condensation reaction of p-phenylbenzaldehyde, butyl acetoacetate and ammonium acetate with a phase transfer catalyst to generate a biphenyl ester dihydropyridine monomer; Step S2-2: using sodium nitrite as an oxidant, catalyzing an organic protonic acid to cause an oxidation reaction of the dihydropyridine group of the biphenyl ester dihydropyridine monomer to generate a biphenyl ester pyridine monomer; Step S2-3: Under alkaline conditions, the carboxylic acid butyl ester functional group of the biphenyl ester pyridine monomer undergoes a hydrolysis reaction to generate a sensitizer I; The preparation method of the sensitizer II is: Step S3-1: using the Hantzsch reaction mechanism, catalyzing the condensation reaction of 4,4'-biphenyldicarboxaldehyde, butyl acetoacetate and ammonium acetate with a phase transfer catalyst to generate a biphenyl bis(ester dihydropyridyl) monomer; Step S3-2: using sodium nitrite as an oxidant, catalyzing an organic protonic acid to cause an oxidation reaction of the dihydropyridine group of the biphenyl bis(ester dihydropyridyl) monomer to generate a biphenyl bis(ester dihydropyridyl) monomer; Step S3-3: Under alkaline conditions, the butyl carboxylate functional group of the biphenyl bis(ester pyridyl) monomer undergoes a hydrolysis reaction to generate a sensitizer II.

2. The process for preparing an environmentally friendly packaging bag material for freeze-dried yogurt fruit particles according to claim 1, characterized in that: The preparation method of the composite film in step 4 is: Step S4-1: using a core-shell structure photosensitizer as a degradation modifier and a low-density polyethylene resin as a raw material, through blending, melting, extrusion, first longitudinally and then transversely stretching, and finally hot pressing to shape, a BOPE surface layer is obtained; Step S4-2: using a core-shell structure photosensitizer as a degradation modifier and ethylene-vinyl alcohol copolymer resin as a raw material, through blending, melting, extrusion, pelletizing, and finally casting into a film, to obtain a barrier intermediate layer; Step S4-3: using a core-shell structure photosensitizer as a degradation modifier and a low-density polyethylene resin as a raw material through blending, melting, extrusion, pelletizing, and finally casting into a film to obtain a PE inner layer; Step S4-4: A high-speed solvent-free laminating machine is used to bond the BOPE surface layer, the barrier middle layer and the PE inner layer to obtain a composite film with a thickness of 80-120 μm.

3. An environmentally friendly packaging bag material for freeze-dried yogurt fruit particles prepared by the process according to any one of claims 1-2, characterized in that: The environmentally friendly packaging bag material for freeze-dried yogurt fruit particles has a tensile strength of 26-30 MPa, an elongation at break of 420-460%, and can be recycled through ultraviolet degradation.

4. Use of the composite film prepared according to the process according to any one of claims 1 to 2 in environmentally friendly packaging of freeze-dried yogurt fruit particles.

Citation Information

Patent Citations

  • A photodegradable environmentally friendly plastic packaging bag and its production process

    CN114044961B

  • Multi-layer degradation film

    CN110126402A

  • Degradable polylactic acid plastic

    CN112080118A